1998
DOI: 10.1212/wnl.51.2.493
|View full text |Cite
|
Sign up to set email alerts
|

Unusual EEG pattern linked to chromosome 3p in a family with idiopathic generalized epilepsy

Abstract: In this family, a characteristic EEG activity is due to the effect of a single gene on chromosome 3p. A gene encoding a Ca2+ channel subunit maps in the interval and is a potential candidate for the trait. The clinical expression of epilepsy in four family members may reflect the interaction of additional genes, though environmental or other factors cannot be excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Another layer of regulation occurs at the ER where GTRAP3-18 and RTN2B regulate the amount of EAAT3 leaving the ER for further processing in the Golgi. Interestingly, GTRAP3-18 was found on a susceptibility locus for epilepsy (Zara et al, 1998). …”
Section: Regulation Of Eaat3mentioning
confidence: 99%
“…Another layer of regulation occurs at the ER where GTRAP3-18 and RTN2B regulate the amount of EAAT3 leaving the ER for further processing in the Golgi. Interestingly, GTRAP3-18 was found on a susceptibility locus for epilepsy (Zara et al, 1998). …”
Section: Regulation Of Eaat3mentioning
confidence: 99%
“…15 Several studies have described the clinical manifestations of epilepsy in single families, or sets of families. These Partial epilepsy with pericentral spikes AD 4p15 25 Familial temporal lobe epilepsy with febrile seizures with digenic inheritance AD 1q and 18q 28 Familial partial epilepsy with variable foci AD 22q11-q12 26 AD = autosomal dominant; AR = autosomal recessive. has been implicated.…”
Section: S34mentioning
confidence: 99%
“…Linkage studies in IGE are difficult, and findings to date remain to be confirmed by replication and identification of the underlying genetic defects. A number of loci have been reported for IGE, including studies of Italian families with evidence for linkage to chromosome 8q (2), non‐JME families to chromosome 8q (4), and another Italian family with an unusual generalized epileptiform EEG trait and IGE to chromosome 3p (5)(Table 1).…”
Section: Genetics Of Generalized Epilepsiesmentioning
confidence: 99%